Análisis de las normas penales en blanco para la tipificación del delito, la aplicación del complemento vulnera el principio de legalidad y seguridad jurídica. - Robles Machuca, Nathaly Paulina (2024)
The present research work titled “Analysis of the blank penal norms for crime classification, the application of the supplement violates the principle of legality and legal certainty”, aims to guarantee the principle of legality and legal certainty as contemplated in the Constitution of the Republic of Ecuador through its current legislation. Therefore, it highlights the existing issue of using blank penal norms as a supplement to another norm to describe criminal conduct or to establish corresponding sanctions. The purpose of this curricular integration work is to emphasize the importance of respecting the principle of legality and legal certainty since blank penal norms often lack clarity and precision, leaving substantial aspects of crime classification or sanctions to secondary norms, thus giving judges and competent authorities the capacity to define what constitutes criminal conduct. For the pertinent development of this work, I have determined several research parameters such as legal, conceptual, and doctrinal. The type of research conducted was based on obtaining documentary sources, primarily doctrine, internal regulations, comparative law, and pronouncements from international bodies. Additionally, necessary methods were used, including inductive, deductive, analytical, exegetical, Socratic, comparative, statistical, and synthetic methods. Regarding fieldwork, techniques such as surveys and interviews were applied, from which I obtained the opinions of professionals and specialists in criminal matters, with the objective of verifying the stated problem and suggesting a solution to avoid the violation of the principle of legality and legal certainty.